Anchoring: Cognitive bias and numerical conception - Kipouràs, Pàvlos (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Anchoring is a cognitive bias connected to the conception of information by every individual. The initial notion created becomes a significant point of reference for all future interpretations of the same object or data, so as to block any further re-elaboration to the initially defined information. The article presents a practical case of a false numerical conception due to anchoring
Keywords: zakotwiczenie; błąd (prawo); koncepcja; morfologia; data; kognitywny